REAL-TIME MEASUREMENT OF VOLCANIC SO2 EMISSIONS: VALIDATION OF A NEW UV CORRELATION SPECTROMETER (FLYSPEC) - Horton K.A.; Williams-jones G.; Garbeil H.; Elias T.; Sutton A.J.; Mouginis-mark P.; Porter J.N.; Clegg S. (My University, 2006)
A miniaturized, lightweight and low-cost UV correlation spectrometer, the FLYSPEC, has been developed as an alternative for the COSPEC, which has long been the mainstay for monitoring volcanic sulfur dioxide fluxes. Field experiments have been conducted with the FLYSPEC at diverse volcanic systems, including Masaya (Nicaragua), Poás (Costa Rica), Stromboli, Etna and Vulcano (Italy), Villarica (Chile) and Kilauea (USA). We present here those validation measurements that were made simultaneously with COSPEC at Kilauea between March 2002 and February 2003. These experiments, with source emission rates that ranged from 95 to 1,560 t d−1, showed statistically identical results from both instruments. SO2 path-concentrations ranged from 0 to >1,000 ppm-m with average correlation coefficients greater than r 2=0.946. The small size and low cost create the opportunity for FLYSPEC to be used in novel deployment modes that have the potential to revolutionize the manner in which volcanic and industrial monitoring is performed.
Keywords: FLYSPEC; VOLCANIC EMISSIONS; ULTRAVIOLET CORRELATION SPECTROMETER